The use of formal criteria to assess psychological models of hallucinations: a systematic review. Issue 3 (3rd July 2019) - Hickey, Tara; Buck, Kimberly; Lao, So-An; Nelson, Barnaby; Meadows, Graham
ABSTRACT: Objectives: Our aim was to explore the application of systematic criteria proposed by Bentall, Corcoran, Howard, Black and Kinderman (2001) to determine whether they are helpful in determining the quality of psychological models, which are used to develop and guide treatment. Method: We chose to conduct a systematic review of models of hallucinations. PsycINFO, MEDLINE and PubMED were used to identify relevant articles. Each model was classified as a high, medium or low level of fit with the criteria. Results: Nineteen models met the inclusion criteria. Two models were a high level of fit, twelve a medium level of fit while the rest were a low level of fit. Some difficulties were encountered applying the criteria and are discussed. Conclusions: Bentall et al.'s (2001) criteria proved useful. Frith's (2015) and Hoffman's (1986) models were deemed the best level of fit. The role of self-monitoring and language-production processes in hallucination formation may merit further investigation. There is an outstanding need for international standardized guidelines to advance the quality of psychological models to assist the design and delivery of more effective interventions.